The US-China Competition and Indonesia’s Stance in ASEAN During Jokowi’s Leadership - Simatupang, Karmel Hebron (Sospol, 2025)
The article examines the stance of Indonesian President Joko Widodo's (Jokowi) administration in the context of competition between the United States and China. Employing a qualitative methodology, the author explores neoliberal theory and the concept of non-alignment to explain the position of the Indonesian government. The data sources were collected from government reports, books, magazines, articles, and news reports. It is noted that the administration of President Jokowi is able to balance its positions against the background of the rivalry between the United States and China in the Asia-Pacific region. The expansion of Indonesia's economic relations with China has increased their economic interdependence due to the fact that Jokowi's policy gives priority to economic diplomacy, focusing on national economic growth and infrastructure development. Despite the fact that economic relations between Indonesia and China continue to expand, Jakarta still adheres to the policy of non-alignment in relations with major world powers, namely, it does not take the side of one party or bloc, and also does not form military alliances with other leading international players. This decision is considered strategic for peace and stability in ASEAN and Southeast Asia.